2021
DOI: 10.1021/acsbiomaterials.1c00387
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Advanced Glycation End Products Associated Structural Changes in Serum Albumin

Abstract: Structural alterations in proteins have a significant impact on their function and body physiology. Glycation via nonenzymatic forms of cross-linking leads to proteins’ conformational changes, the macromolecule being recognized as a stable fibrillary structure, oligomerization, and becoming advanced glycation end products (AGEs). Protein that undergoes glycation-related modifications, namely, β-sheet enriched structural changes, are recognized as amyloid. In the current study, we characterized a single protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Oligomerization can be accompanied by significant conformational changes which are significant for RAGE-dependent neutrophil responses. Thus, lately it was shown that modification of BSA influences the stiffness and formation of β-rich fibrils [ 39 ], which are well-known RAGE agonists [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oligomerization can be accompanied by significant conformational changes which are significant for RAGE-dependent neutrophil responses. Thus, lately it was shown that modification of BSA influences the stiffness and formation of β-rich fibrils [ 39 ], which are well-known RAGE agonists [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the ECM protein’s profile and structural changes can be facilitated by forming advanced glycation products (AGEs) from protein cross-linking via a non-enzymatic glycation process [ 11 ]. As we recently reported for serum albumin, the formation of AGEs and subsequent protein cross-linking increases the stiffness of the protein [ 12 ]. In cellular models and tissues, the accumulation of AGEs affects their activity, signaling pathways, and function [ 13 ].…”
Section: Introductionmentioning
confidence: 89%
“…Dissected VAT from CHD and HFD-fed mice were measured as was previously described [ 12 ]. The tissues were measured on an HR-3 hybrid Rheometer (TA Instruments, New Castle, DE, USA) used a 8-mm diameter parallel Peltier plate at 25 °C or 37 °C according to ISO 6721-1 method to measure the viscoelasticity and determine the rheological properties of VAT.…”
Section: Methodsmentioning
confidence: 99%
“…Modification of lysine and arginine during AGE formation renders the protein surface negatively charged, which enables binding to RAGE and amplifies RAGE–mediated inflammation and adhesion. Recently, Nafty et al demonstrated that glycation alters the helical conformation of serum albumin and promotes the formation of β–sheets enriched with amyloid fibrils ( Naftaly et al, 2021 ). Serum albumin becomes insoluble and aggregates during co–incubation with methylglyoxal, glycolaldehyde ( Naftaly et al, 2021 ) and ribose–modified albumin, thereby forming amyloid–like aggregates that induce cytotoxicity ( Wei et al, 2009 ), which is linked to the development of Alzheimer’s disease ( Tu et al, 2016 ).…”
Section: In Vivo Formation Of Agementioning
confidence: 99%
“…Recently, Nafty et al demonstrated that glycation alters the helical conformation of serum albumin and promotes the formation of β–sheets enriched with amyloid fibrils ( Naftaly et al, 2021 ). Serum albumin becomes insoluble and aggregates during co–incubation with methylglyoxal, glycolaldehyde ( Naftaly et al, 2021 ) and ribose–modified albumin, thereby forming amyloid–like aggregates that induce cytotoxicity ( Wei et al, 2009 ), which is linked to the development of Alzheimer’s disease ( Tu et al, 2016 ). There are a wide variety of pathways involved in the formation of AGEs and the other RAGE ligands.…”
Section: In Vivo Formation Of Agementioning
confidence: 99%